Mitochondrial calcium buffering depends upon temperature and is associated with hypothermic neuroprotection against hypoxia-ischemia injury. - Sergey Sosunov; Arnav Bhutada; Zoya Niatsetskaya; Anatoly Starkov; Vadim Ten (PLoS ONE, 2022)
Hypothermia (HT) is a standard of care in the management of hypoxic-ischemic brain injury (HI). However, therapeutic mechanisms of HT are not well understood. We found that at the temperature of 32°C, isolated brain mitochondria exhibited significantly greater resistance to an opening of calcium-induced permeability transition pore (mPTP), compared to 37°C. Mitochondrial calcium buffering capacity (mCBC) was linearly and inversely dependent upon temperature (25°C-37°C). Importantly, at 37°C cyclosporine A did not increase mCBC, but significantly increased mCBC at lower temperature. Because mPTP contributes to reperfusion injury, we hypothesized that HT protects brain by improvement of mitochondrial tolerance to mPTP activation. Immediately after HI-insult, isolated brain mitochondria demonstrated very poor mCBC. At 30 minutes of reperfusion, in mice recovered under normothermia (NT) or HT, mCBC significantly improved. However, at four hours of reperfusion, only NT mice exhibited secondary decline of mCBC. HT-mice maintained their recovered mCBC and this was associated with significant neuroprotection. Direct inverted dependence of mCBC upon temperature in vitro and significantly increased mitochondrial resistance to mPTP activation after therapeutic HT ex vivo suggest that hypothermia-driven inhibition of calcium-induced mitochondrial mPTP activation mechanistically contributes to the neuroprotection associated with hypothermia.